Classroom finder system with student availability, space and time constraint - Loh, Yong Bin (2024)
In every educational institution, the process of conducting student assessments is very important to evaluate students' academic progress, understanding and performance. A crucial aspect of this process is the allocation of suitable rooms for the academic activities. However, the traditional approach of manually allocating rooms is labour-intensive and prone to errors, particularly when considering constraints such as student availability, space requirements and scheduling conflicts. Therefore, an automate Classroom Finder System is developed to automate the room finding and allocation for student assessments. The primary focus of the system is on facilitating efficient and conflict-free room assignments while considering various constraints and requirements by exploring the suitable Artificial Intelligence approaches and scheduling algorithms. Therefore, the project scopes are to identify the specific constraints and requirements to be considered in the Classroom Finder System and also explore the suitable Artificial Intelligence approaches and room allocation and scheduling algorithms. The project is also aimed to implement real-time management, communication and updates of the assessment and room details to provide instant updates and notifications. Scrum methodology was selected for the development methodology of this project while the tools of HTML, CSS, JavaScript, Bootstrap, Jinja2 Template Engine, Flask, SQLite and VS Code are used in the development of this project. In the end of project, the unit testing, user acceptance testing, and usability testing has also been conducted to test the system. In conclusion, all the objectives are achieved, and limitations are analysed while recommendations for future enhancements are discussed.